Microencapsulation as a tool to producing an extruded functional food. (June 2020) - Favaro-Trindade, Carmen S.; Patel, Bhavesh; Silva, Marluci P.; Comunian, Talita A.; Federici, Enrico; Jones, Owen G.; Campanella, Osvaldo H.
Abstract: Cooking-extrusion is a technology used in the production of many foods, including breakfast cereals and snacks. However, the use of some ingredients and additives in the formulations remains a challenge, due to the high temperature and shear conditions employed during this process. Complex coacervation remains an unexplored encapsulation technique to protect sensitive ingredients during extrusion. The aim of this study was to produce extruded product enriched with proanthocyanidin-rich cinnamon extract (PRCE) in free and encapsulated forms, with the purpose of evaluating the efficiency of the encapsulation process to protect these bioactive compounds during extrusion. Extrusion alters total carotenoids from cornmeal (16.95 μg/g for cornmeal and from 2.08 to 8.83 μg/g for extruded control treatments), total phenolics (retention values from 18.56 to 26.94% and 39.28–78.34% for extruded with free and encapsulated PRCE, respectively), and total proanthocyanidins contents (retention values from 9.59 to 14.65% and 25.86–45.78% for extruded with free and encapsulated PRCE, respectively). Microencapsulation by complex coacervation is an efficient method to protect PRCE compounds during extrusion process, being the extruded products with encapsulated PRCE produced at 130 °C, shear rate of 1000/s and 500/s and residence time of 0.128 s and 0.256 s the ones which presented more protection during their storage. Highlights: The effect of the temperature of extrusion was clear for bioactive retentions. Extrusion alters total phenolics and proanthocyanidins for extruded products. Encapsulation is effective for protection of bioactive during extrusion.